Synthesis, characterization and molecular docking of new C, N‐palladacycles containing pyridinium‐derived ligands: DNA and BSA interaction studies and evaluation as anti‐tumor agents. (22nd January 2019) - Karami, Kazem; Jamshidian, Nasrin; Zakariazadeh, Mostafa
Abstract : Four new monomeric Pd (II) complexes with formulas [Pd(C, N)‐(2′‐NH2 C6 H4 )C6 H4 (N3 )(L)] (A ), (B ) and [Pd(C, N)‐C6 H4 CH2 NH(C4 H9 )(N3 )(L)] (C ), (D ), [L = isonicotinamide for (A ) and (C ), L = 4‐N, N‐dimethylaminopyridine for (B ) and (D )] have been synthesized using four initial dimers [Pd2 {(C, N)‐(2′‐NH2 C6 H4 )C6 H4 }2 (μ‐OAc)2 ] (1 ), [Pd2 {(C, N)‐ (2′‐NH2 C6 H4 )C6 H4 }2 (μ‐N3 )2 ] (3 ) forA andC, and [Pd2 {(C, N)‐C6 H4 CH2 NH(C4 H9 )}2 (μ‐OAc)2 ] (2 ) and [Pd2 {(C, N)‐C6 H4 CH2 NH(C4 H9 )}2 (μ‐N3 )2 ] (4 ) forB andD . Then synthesized complexes have been characterized by Fourier transform‐infrared, NMR spectroscopy and thermal gravimetric‐differential thermal analysis. Furthermore, UV–Vis spectroscopy, fluorescence spectroscopy, circular dichroism (CD) and helix melting temperature measurements have been employed to study the binding interaction of them with calf thymus‐deoxyribonucleic acid (DNA). The results reveal that all synthesized complexes can interact with DNA via groove‐binding mode. Bovine serum albumin (BSA)‐binding studies have been carried out using UV–Vis spectroscopy, emission titration and CD. However, competitive binding studies using warfarin, ibuprofen and digoxin on site markers demonstrated that the complexes bind to different sites on BSA. The results also indicated that the binding site was mainly located within site‐III for complexA, and site‐I for complexesB, C andD of BSA. In addition, molecular docking studies have been executed to determine the binding site of the DNA and BSA with complexes. Eventually, in vitro cytotoxicity of synthesized palladium complexes and cisplatin were carried out against human promyelocytic leukemia cancer (Hela) and breast cancer (MCF‐7) cell lines. Pursuant to the IC50 values, the cytotoxicity of complexes against MCF‐7 was more than Hela. Abstract : Four new monomeric Pd (II) complexes have been synthesized and characterized by several spectroscopic methods. Then binding interaction studies of them with calf thymus‐deoxyribonucleic acid reveal that all synthesized complexes can interact with it via groove binding mode. BSA binding studies demonstrated that the complexes bind to different sites on BSA with high affinity. Finally, In vitro cytotoxicity was carried out against human promyelocytic leukemia cancer (Hela) and breast cancer (MCF‐7) cell lines.